2016
DOI: 10.1002/poc.3669
|View full text |Cite
|
Sign up to set email alerts
|

Exploring acetylene chemistry in superbasic media: A theoretical study of the effect of water on vinylation and ethynylation reactions with acetylene in KOH/DMSO and NaOH/DMSO systems

Abstract: A rapidly developing approach adding new dimensions to acetylene chemistry relying on employment of high basicity media such as alkali metal hydroxide suspensions in dimethyl sulfoxide (DMSO) has been, for the first time, investigated theoretically using ab initio models. Extending our recently introduced model of superbase catalysis with a nondissociated KOH (or NaOH) participation, we present here a model for a superbasic reaction center with the first solvation shell explicitly included. The alkali metal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 79 publications
0
32
0
Order By: Relevance
“…Previously, we proposed a general concept of superbase (KOH/DMSO and KOBu t /DMSO) catalysis . According to this concept, the reaction center is represented by a nondissociated molecule of KOH or KOBu t , whose environment can be described by models of various levels of complexity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we proposed a general concept of superbase (KOH/DMSO and KOBu t /DMSO) catalysis . According to this concept, the reaction center is represented by a nondissociated molecule of KOH or KOBu t , whose environment can be described by models of various levels of complexity.…”
Section: Resultsmentioning
confidence: 99%
“…According to this concept, the reaction center is represented by a nondissociated molecule of KOH or KOBu t , whose environment can be described by models of various levels of complexity. The most complete description of the reaction center includes the nearest solvation shell: the pentasolvate model ( PENTA ) for potassium complexes—KOH·5DMSO, KOBu t ·5DMSO (Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that in the superbase‐catalyzed reactions, the catalyst (KOH/DMSO) can be approximated by the stable complexes of 5DMSO·KOH, in which K + is located in closest pseudooctahedral surrounding formed by DMSO oxygen atoms and hydroxide ions (pentasolvate model) …”
Section: Introductionmentioning
confidence: 99%
“…According to the pentasolvate model, the activation barrier of addition to the triple bond СС of a methoxide‐ion ( O ‐vinylation) is estimated to be by 3.0 kcal/mol higher than that of acetone carboanion ( C ‐vinylation) . The anionic model shows that this difference does not almost change and this value is 2.6 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%